2011
DOI: 10.14210/bjast.v15n1.p79-93
|View full text |Cite
|
Sign up to set email alerts
|

Variação temporal do microfitoplâncton no Canal Estuarino de Santos (SP)

Abstract: An increase in abundance of potentially toxic dinoflagellates in the Santos channel, located in a highly urbanized and eutrophic estuarine complex, was reported in the literature. Prediction of such occurences is essential, but phytoplankton community structure in dynamic estuarine systems are difficult to analyze. In the present work, we attempted to discuss microphytoplanktonic community in relation to physical variables looking for shifts in composition, in time scales of 25 hours. To achieve our goal two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…T. musica and G. balticum are tycoplanktonic estuarine diatoms. Both species are present in other tropical estuaries in Brazil (Fujita and Odebrecht 2007;Leão et al 2008;Santiago et al 2010;Masuda et al 2011), while F. capucina is the only tycoplanktonic freshwater form in the present study, commonly reported in other benthonic substrates (Roberts et al 2004;Antoniades et al 2005). The three diatoms mentioned are in water column due to the high dynamism of the estuarine ecosystem, which induces mixture and resuspension of organisms from the bottom (Fujita and Odebrecht 2007).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…T. musica and G. balticum are tycoplanktonic estuarine diatoms. Both species are present in other tropical estuaries in Brazil (Fujita and Odebrecht 2007;Leão et al 2008;Santiago et al 2010;Masuda et al 2011), while F. capucina is the only tycoplanktonic freshwater form in the present study, commonly reported in other benthonic substrates (Roberts et al 2004;Antoniades et al 2005). The three diatoms mentioned are in water column due to the high dynamism of the estuarine ecosystem, which induces mixture and resuspension of organisms from the bottom (Fujita and Odebrecht 2007).…”
Section: Discussionsupporting
confidence: 54%
“…These species are transported downstream by the river's flow (Masuda et al 2011). The occurrence of some freshwater cyanobacteria species in our study show that these species are present in some freshwater ecosystems in Northeast Brazil, mostly in rivers and reservoirs that are components of the watershed of the Capibaribe River (Dantas et al 2012).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It is a cosmopolitan and euryhaline species, one of the most abundant in estuaries, considered opportunistic in eutrophic environments TENEBAUM, 2010;MASUDA et al, 2011;REZENDE et al, 2015;BARRERA-ALBA et al, 2016). Skeletonema costatum is classified as a harmful species and it is associated with toxic microorganisms in some cases, causing economic losses for aquaculture (KHAN et al, 1998;UNESCO, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Estuaries are hydrodynamic coastal environments, where the freshwater flow of rivers is mixed with the salt water from the oceans causing extensive environmental fluctuations (NASCIMENTO et al, 2003;MASUDA et al, 2011). Those conditions create a biologically productive system, considered "hotspots" in the cycling and export of nutrients, increasing the rates of biological metabolism and the local primary production CALLAWAY et al, 2014;CLOERN et al, 2014).…”
Section: Introductionmentioning
confidence: 99%